A Meta-Theoretical Systematic Review of the Culture-Centered Approach to Health Communication: Toward a Refined, "Nested" Model. Issue 3 (29th November 2019) - Sastry, Shaunak; Stephenson, Megan; Dillon, Patrick; Carter, Andrew
Abstract: While the influence of the culture-centered approach (CCA; Dutta, 2008 ) on health communication scholarship is undeniable, there has been no evaluation of its application in the field. Guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for systematic reviews (Moher, Liberati, Tetzlaff & Altman, 2009 ), we analyzed a corpus of empirical, peer-reviewed literature ( n = 47) that used the CCA. Our findings demonstrate that (a) the ontological axis of the CCA (culture, structure, and agency) was widely used as a heuristic for defining health problems; and (b) studies varied widely in their adoption of the CCA's epistemological axis (that of dialogic co-construction with marginalized communities), either at the level of problem definition, problem interpretation, and/or community participation. Finally, while most studies reported self-reflexivity in design, we coded for methodological and philosophical reflexivity to assess fidelity to the CCA axiology. Based on the variations and consistencies in its use, we offer a refined, "nested" conceptualization of the CCA.